Adaptation of semiotic theory in Neo-Chinese interior design / Xu Kewei, Azlaini Abdul Aziz and Arniatul Aiza Mustapha - Xu, Kewei; Abdul Aziz, Azlaini; Mustapha, Arniatul Aiza (College of Built Environment, 2023)
Globalization has inevitably distrupted the sanctity of the local culture of countries in the world under the impact of dominant foreign culture.